Influence of gas supply changes on the formation process of complex mixed gas hydrates - Pan, Mengdi (Dr.); Schicks, Judith Maria (PD. Dr. habil.) (Molecules, 2021)
Natural gas hydrate occurrences contain predominantly methane; however, there are increasing reports of complex mixed gas hydrates and coexisting hydrate phases. Changes in the feed gas composition due to the preferred incorporation of certain components into the hydrate phase and an inadequate gas supply is often assumed to be the cause of coexisting hydrate phases. This could also be the case for the gas hydrate system in Qilian Mountain permafrost (QMP), which is mainly controlled by pores and fractures with complex gas compositions. This study is dedicated to the experimental investigations on the formation process of mixed gas hydrates based on the reservoir conditions in QMP. Hydrates were synthesized from water and a gas mixture under different gas supply conditions to study the effects on the hydrate formation process. In situ Raman spectroscopic measurements and microscopic observations were applied to record changes in both gas and hydrate phase over the whole formation process. The results demonstrated the effects of gas flow on the composition of the resulting hydrate phase, indicating a competitive enclathration of guest molecules into the hydrate lattice depending on their properties. Another observation was that despite significant changes in the gas composition, no coexisting hydrate phases were formed.